1960년대 초반 북중관계 밀착 연구 - 한상준 (중국근현대사연구, 2022)
The early 1960s was a time when North Korea-China honeymoon relations reached their peak. However, most of the studies so far examining the background and causes of the close relationship between North Korea and China show limitations in that they have been limited to small and medium-sized disputes. Therefore, this paper conducted an analysis and review of the closeness of North Korea-China relations in the early 1960s with the intention to overcome such limitations and supplement the deficiencies of existing studies, and the following conclusions were drawn. First, it was confirmed that North Korea-China secret relations in the early 1960s developed on the continuity of the friendly bilateral relations that had already been established at the end of the 1950s, and that there was an inertia of close relations between North Korea and China that had continued since the late 1950s. In fact, it could be said that North Korea-China relations reached the highest point in 1958, when the Chinese military withdrawal was finally completed. The complete withdrawal of Chinese troops was also an event that simultaneously showed the uniqueness and robustness of bilateral relations between North Korea and China in the late 1950s. The fact that China's internal decision to withdraw its troops at the end of 1956 was a symbolic measure that it changed its policy toward North Korea from a ‘interference policy’ to a ‘non-interference policy’. The change in North Korea policy promoted by China had an impact. Second, the context and flow of the small and medium-sized disputes surfaced, which became the international background and condition for close relations between North Korea and China in the early 1960s, were reviewed in detail from 1958. Although some researchers have paid attention to a series of situations that occurred in 1958 while conducting the analysis of the small and medium-sized conflict, there are not many studies on small and medium-sized conflicts in Korean academic circles. explanation was insufficient. Third, the background and causes of close relations between North Korea and China in the early 1960s were explored through analysis of the international conditions and environment that China faced. In the sense that studies examining the closeness of North Korea-China relations in the early 1960s were not actively attempted from China's position and situation, this paper contributed to broadening the perspectives and perspectives of related studies. In fact, from the late 1950s to the early 1960s, the environment and conditions of the international situation surrounding China were very unfavorable to China. China faced the Soviet threat from the northwest, the Indian threat from the southwest, and the American threat from the south, and China's national security was in a very unstable state.
Keywords: 中朝关系; 中苏分裂; 和平共处; 社会主义阵营; 国际工产注意运动; North Korea-China Relations; Sino-Soviet Conflict; Peaceful Coexistence; Socialist Camp; International Communist Movement; 북중관계; 중소갈등; 평화공존; 사회주의 진영; 국제공산주의 운동